The efficacy of fenbendazole on horse strongyle infestation from Bazosul nou - Morariu S.,; Darabus Gh.,; Oprescu I.,; Narcisa Mederle,; Ilie M.,; Milutin C.,; Florica Morariu,; Stepanescu D. (Medicamentul Veterinar, 2007)
In the last few years horse strongyles became very important because they are harmful and prejudicious for horses and horse owners. The large number of strongyle species and the possibility of apparition ofbenzimidazole compounds resistance phenomenon were on the basis of this study. After administration of 10% fenbendazole (Panacur) to randomic selected horses from Bazosul Nou, the efficacy of the anthelmintic by classical method FECRT and supplementary, by Borgsteede and Presidente relations, was calculated. The anthelmintic efficacy was over 99% by the mean of all three methods. The faeces examination from treated horses revealed the presence of 19 species of strongyles.